(untitled) (LEARNing Landscapes, 2012)
This study examines events within a CoLab1 3RDSpace: Summer Leadership Institute on Creativity & Innovation. The analyses are organized into two telling cases and reveal how participants develop a shared understanding of ResponsiveDesign, CoLab’s theory of inquiry and innovation. Drawing on an interactional ethnographic perspective, the analyses make visible the ways in which concepts of space, language, creativity, and innovation complement one another to form ResponsiveDesign as a powerful approach for educators in any setting to transform their ordinary places into extraordinary spaces for creatively confident learning.